INFLUENCE OF EMULSIFICATION METHODS AND SPRAY DRYING PARAMETERS ON THE MICROENCAPSULATION OF TURMERIC OLEORESIN - FERREIRA, S.; MALACRIDA, C. R.; NICOLETTI, V. R. (Emirates Journal of Food and Agriculture, 2019)
Turmeric (Curcuma longa L.) oleoresin possess valuable phenolic compounds that are susceptible to degradation, and microencapsulation is a powerful technique to increase its stability. Emulsification is a preponderant step in microencapsulation of hydrophobic compounds and physical-chemical properties of the parent emulsion affects effectiveness of spray-drying process and functional properties of the produced microcapsules. The present work aimed to evaluate the influence of emulsion formulation, emulsification methods, and spray-drying operational conditions on the encapsulation efficiency of turmeric oleoresin using maltodextrin/gelatin blends as wall material. The effects of different concentrations of maltodextrin (12 - 31.7 wt %) and gelatin (0.6 - 6 wt %), combined with three methods of emulsification - high shear homogenization with and without emulsifier addition, and sonication – were evaluated regarding emulsion droplet mean diameter and stability. Based on the results, an emulsion formulated with 26 g of maltodextrin and 0.6 g of gelatin per 100 g of emulsion was selected to study the influence of spray drying conditions - drying-air temperature (124 – 190 oC), atomization airflow (275 – 536 L h-1), and emulsion feeding flow (1.4 – 8.6 mL min-1) - on encapsulation efficiency, water content, and solubility of turmeric oleoresin microcapsules. Sonication resulted in higher emulsion stability and, although drying-air temperature did not affect significantly the microcapsule properties, the best set of spray drying conditions was drying-air at 160 ºC, atomization airflow of 420 L h-1, and emulsion feeding flow of 6 mL min-1. Combinations of higher atomization airflow and lower emulsion feeding flow resulted in lower values of curcumin encapsulation efficiency.